CLASS ACTION AS A FORM OF COMMUNITY PARTICIPATION IN ENVIRONMENTAL LAW ENFORCEMENT - TJAHJANI, JOEJOEN; Fajarwati, Maulidiyah; Diyassandra, Vera Anggie (Universitas Islam Lamongan, 2021)
ABSTRACTÂ Class action on environmental law enforcement is related to community participation as stated in Article 91 of the Law on Environmental Protection and Management No. 32 of 2009. The right to participate is recognized as a way to get the right to a good and healthy environment. The community is given access to participate in activities that can or have had an impact on the environment and in law enforcement.